High hydrostatic pressure treatments trigger de novo carotenoid biosynthesis in papaya fruit (Carica papaya cv. Maradol). (30th March 2019) - Ramos-Parra, Perla A.; García-Salinas, Carolina; Rodríguez-López, Carlos E.; García, Noemí; García-Rivas, Gerardo; Hernández-Brenes, Carmen; Díaz de la Garza, Rocío I.
Highlights: HHP treatment is an oxidative stress elicitor on papaya fruit cubes. Carotenoid levels were significantly increased in stored HHP-treated. Lycopene contents rise up to 11-fold after mild HHP and 2-day storage. Phytoene desaturase gene expression was upregulated after mild HHP treatment. HHP triggers de novo carotenoid biosynthesis as a stress response in vegetables. Abstract: High hydrostatic pressure (HHP) processing is a non-thermal technology reported to increase desirable metabolites in plant foods. This work evaluated changes in carotenoid accumulation in fresh-cut papaya fruit as affected by HHP treatment (50–400 MPa for 3–60 min) and during subsequent storage at 4 °C; simultaneously, transcriptional activities of carotenoid biosynthetic genes and oxidative stress markers were evaluated. LC–MS analyses revealed that HHP treatment increased carotenoid precursors and carotenes contents following processing and storage: lycopene levels increased up to 11-fold compared to the non-treated samples, and H2 O2 and lipid peroxidation were concomitantly increased. qRT-PCR of intact RNA showed that the amount of phytoene desaturase transcripts increased after HHP treatment, and that they were correlated with carotene accumulation. This is the first study to show that HHP treatment triggers de novo carotenoid biosynthesis, which is regulated at the transcriptional level, possibly by inducing oxidative stress signaling in fruit tissue.